THREE-DIMENSIONAL SOIL PROFILE IMAGEMENT IN THE MANDALIKA CIRCUIT AREA WITH ROCKWORKS SOFTWARE AS FOUNDATION DESIGN CONSIDERATIONS - Chandra, Fani Adhi (Universitas Negeri Malang, 2022)
Abstract: Soil investigation work is considered less important in the project because it lacks added value in the short term, therefore it will be kept to a minimum in order to reduce costs. In the implementation of the construction of the international Mandalika circuit project, there was a problem that became a reference for research, namely when the development process was running the owner asked for a new supporting building to be made. This requires the contractor to conduct a soil investigation to obtain a Soil Profile in the area. As an effort to make work efficiency and accuracy, the use of Rockworks software is very appropriate to be used in supporting soil investigation work to obtain soil profiles in the project. The data used in this study is data from field tests in the form of sondir and SPT drill data in the Mandalika circuit area. The data serves as input material for the Rockworks software in processing the data so that the overall soil profile is obtained through the interpolation method by the Rockworks software. In this study, there were 20 sondir and drill data points scattered in the Mandalika circuit area. From this data, it is processed using Rockworks software so that the overall soil profile input obtained can then be selected and presented in the area where the new supporting building will be built. In the presentation of the results of the software output, it can be divided into two parts, namely the three-dimensional model of the state of the soil profile below the surface and the cross-section generated from the three-dimensional model. The results of this study indicate that there are seven types of stratigraphy or layers produced using Rockworks software interpolation in the Mandalika circuit area. The layer consists of Silt-Hard, Clay-Stiff, Clay-Hard, Sand-Medium Dense, Sand-Dense, Sand-Very Dense, and Andesite soils which are scattered and form a subsurface profile in the Mandalika circuit area. The dominant layer is sand or sand, considering that the Mandalika circuit area is located on the shoreline, the rest can be found in layers of clay or clay and silt or silt. The building area shows that there are 5 types of soil, namely Clay-Stiff, Clay-Hard, Sand-Medium Dense, Sand-Dense, and Sand-Very Dense. In the track lane area, there are 4 types of soil, namely Clay-Stiff, Clay-Hard, Sand-Dense, and Sand-Very Dense.Keywords: soil investigation, soil profile, Rockworks software, Mandalika circuit project, three-dimensional model.